2004
DOI: 10.1111/j.1365-2249.2004.02686.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolactin and cortisol on natural killer (NK) cell surface expression and function of human natural cytotoxicity receptors (NKp46, NKp44 and NKp30)

Abstract: SummaryThe surface density of the triggering receptors (e.g. NKp46 and NKp30) responsible for natural killer (NK) cell-mediated cytotoxicity determines the ability of NK cells to kill susceptible target cells. In this study, we show that prolactin up-regulates and cortisol down-regulates the surface expression of NKp46 and NKp30. The prolactin-mediated activation and the cortisol-mediated inhibition of natural cytotoxicity receptor (NCR) surface expression reflects gene regulation at the transcriptional level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 49 publications
2
52
0
1
Order By: Relevance
“…The activity of NK cells is also known to be changed by acute psychological stress (42) and to be reduced by an increase in cortisol levels (43). In the present study, NK cell activity was maintained at a relatively high level during the preexamination period but was reduced immediately after the examination in the two groups.…”
Section: Discussionsupporting
confidence: 52%
“…The activity of NK cells is also known to be changed by acute psychological stress (42) and to be reduced by an increase in cortisol levels (43). In the present study, NK cell activity was maintained at a relatively high level during the preexamination period but was reduced immediately after the examination in the two groups.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, cortisol downregulates the expression of NKp30. 86 Our data are interesting because NKp30 acts together with NKp46 to induce cytotoxic activity against a variety of target cells. These results have important implications for the understanding of the involvement of NK cells in the susceptibility of pregnant women to P. falciparum malaria.…”
Section: Cortisol Prolactin and Susceptibility Of Pregnant Women To mentioning
confidence: 98%
“…Nevertheless, we and others have demonstrated that the surface expression and function of the triggering receptors responsible for NK-mediated recognition and killing of tumor cells is regulated by hormones. 85,86 Prolactin selectively upregulates the surface expression of NKp46 and NKp30. In contrast, cortisol downregulates the expression of NKp30.…”
Section: Cortisol Prolactin and Susceptibility Of Pregnant Women To mentioning
confidence: 99%
“…The killing of K562 cells by fresh human NK cells is mediated mainly by the NKp46 receptor (59,70,71). To define the specificity of the effect of HA on NK cell activity, we further examined the redirected cytotoxicity of NK cells, which is induced by the monoclonal antibody against a specific receptor and therefore reflects the specific receptormediated cytotoxicity.…”
Section: Influenza Virus Ha Binds Nk Cells Through Sialic Acidmentioning
confidence: 99%